Programmable nanodisc patterning by DNA origami - Zhang, Zhao (Nano Lett, 2020)
Nanodiscs (ND) are soluble phospholipid bilayers bounded by membrane scaffold proteins; they have become invaluable in the study of membrane proteins. However, this multifunctional tool has been used individually, and applications involving multiple NDs and their interactions have fallen far behind their counterpart membrane model system: liposomes. One major obstacle is the lack of reliable methods to manage the spatial arrangement of NDs. Here we sought to extend the utility of NDs by organizing them on DNA origami. NDs constructed with DNA-anchor amphiphiles were placed precisely and specifically into these DNA nanostructures via hybridization. Four different tethering strategies were explored and validated. A variety of geometric patterns of NDs were successfully programmed on origami, as evidenced by electron microscopy. The ND ensembles generated in this study provide new and powerful platforms to study protein-lipid or protein-protein interactions with spatial control of membranes.